Czech Republic : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper examines recent developments in inflation and its key determinants in the Czech Republic, with particular focus on the role of wages. A simple analytical framework is presented that relates inflation to wages, import prices, and money, and the interaction of inflation with these variables is then examined empirically in the context of a vector autoregression model. The findings confirm the critical influence of wages, exchange rate changes, and money growth. The paper also analyzes developments in the public finance.